Meningkatkan Kemampuan Penalaran Matematis Siswa dengan Menggunakan Pendekatan Matematika Realistik (PMR) di Kelas VII - Beatrix Anela Silitonga; Zul Amry (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to improve students' mathematical reasoning abilities by using students' realistic mathematical approach to the material of plane figures, quadrilaterals, triangles. This type of research is classroom action research which consists of 2 cycles. The subjects of this research were students in class VII-8 of SMP Negeri 31 Medan, consisting of 32 students. The instruments used in this research were initial test sheets, mathematical reasoning ability test sheets and observation sheets. After the research was carried out for 2 cycles, the results of this research showed that there was an increase in student learning outcomes. This is indicated by the average value in cycle I being 78.78 to 87.28 in cycle II. Meanwhile, the percentage of classical completion increased from cycle I, namely 62.5% to 87.5% in cycle II, so it can be seen that this research has met the specified success indicators. Based on the results obtained, it can be concluded that: 1) the mathematical reasoning abilities of class VIII-1 students at SMPN 31 Medan increased after implementing a learning process with a realistic mathematical approach. 2) by applying a realistic mathematical approach to the learning process, students' mathematical reasoning abilities increase until they reach classical mastery.